Peran Guru dalam Mendeteksi dan Membantu Penanganan Gangguan Psikososial Peserta Didik di Usia Sekolah Dasar - Nuraini Yuni Widiyastuti; Fitri Nurmahmudah (Departement of Mathematics Education, 2023)
Psychosocial disorders can be experienced throughout human life, teachers as second parents in schools need skills and experience to be able to detect psychosocial disorders in students in their class. Schools cannot work alone but must cooperate with parents and relevant agencies authorized to handle psychosocial disorders of students. This study aims to determine the efforts made by the schools in helping the handling of psychosocial disorders experienced by students. In this study using qualitative methods with data collection techniques in the form of interviews and documentation. It can be concluded that it is important for teachers to have the ability to detect psychosocial disorders of students. Good cooperation between schools and parents will make it easier to help deal with psychosocial disorders of students by directing treatment to the authorities, namely psychologists/psychiatrists through public health centers, hospitals and disability services. Teachers play an important role as long as students undergo the handling process by the relevant agencies by creating a conducive and fun learning environment.